MySQL in 10 minutes - Newman, Chris (Sams teach yourself., 2006)
Now at over 5 million downloads and widely used at all levels, MySQL continues to grow in popularity. Readers are hungry for a concise, easily accessible tutorial on MySQL basics that allows them to get up and running quickly. While there are many MySQL books on the market, there are no up-to-date books that meet this need for the reader. Furthermore, sales of MySQL books clearly shows the need for a concise, handy tutorial versus the more bulky introductions to MySQL. Sams Teach Yourself MySQL in 10 Minutes provides a no-fluff, just-the-answers guide to building and managing MySQL databases.